FOXO1 cooperates with C/EBPδ and ATF4 to regulate skeletal muscle atrophy transcriptional program during fasting. Issue 2 (21st January 2022) - Oyabu, Mamoru; Takigawa, Kaho; Mizutani, Sako; Hatazawa, Yukino; Fujita, Mariko; Ohira, Yuto; Sugimoto, Takumi; Suzuki, Osamu; Tsuchiya, Kyoichiro; Suganami, Takayoshi; Ogawa, Yoshihiro; Ishihara, Kengo; et al.
Abstract: Catabolic conditions, such as starvation, inactivity, and cancer cachexia, induce Forkhead box O (FOXO) transcription factor(s) expression and severe muscle atrophy via the induction of ubiquitin–proteasome system‐mediated muscle proteolysis, resulting in frailty and poor quality of life. Although FOXOs are clearly essential for the induction of muscle atrophy, it is unclear whether there are other factors involved in the FOXO‐mediated transcriptional regulation. As such, we identified FOXO–CCAAT/enhancer‐binding protein δ (C/EBPδ) signaling pathway as a novel proteolytic pathway. By comparing the gene expression profiles of FOXO1‐transgenic (gain‐of‐function model) and FOXO1, 3a, 4 –/– (loss‐of‐function model) mice, we identified several novel FOXO1‐target genes in skeletal muscle including Redd1, Sestrin1, Castor2, Chac1, Depp1, Lat3, as well as C/EBPδ. During starvation, C/EBPδ abundance was increased in a FOXOs‐dependent manner. Notably, knockdown of C/EBPδ prevented the induction of the ubiquitin–proteasome system and decrease of myofibers in FOXO1‐activated myotubes. Conversely, C/EBPδ overexpression in primary myotubes induced myotube atrophy. Furthermore, we demonstrated that FOXO1 enhances the promoter activity of target genes in cooperation with C/EBPδ and ATF4. This research comprehensively identifies novel FOXO1 target genes in skeletal muscle and clarifies the pathophysiological role of FOXO1, a master regulator of skeletal muscle atrophy.